The dynamics of industrial employment in Mato Grosso do Sul (2009-2019) (Gestão & Regionalidade, 2024)
The purpose of this article is to analyze the concentration of industrial employment in Mato Grosso do Sul between 2009-2019. In specific and methodological terms, the Location Quotient (QL), Redistribution Coefficient (CR), Location Coefficient (CL) and Relative Employment Participation (PR) of the industrial sector in Mato Grosso do Sul in the period 2009-2019 were used, with in order to analyze the dynamics of that segment. Among other reasons, the present work is justified by the lack of publications using the mentioned methods, to the industrial sector and to the state of Mato Grosso do Sul, updated for the period 2009-2019. Furthermore, in addition to being one of the UN's sustainable development goals (ninth), the industrial segment represents a significant production chain, capable of generating employment and income. The results found show that the region of Pantanal, Bodoquena and Aquidauana remain as the most prominent in mineral extraction, unlike the transformation industry that has greater sprawl in the state.
Keywords: Industrial Economics; Annual List of Social Information; Location Quotient; Redistribution Coefficient; Location Coefficient